DAMPAK GREENWASHING TERHADAP INVESTASI KEBERLANJUTAN SERTA PERAN AUDIT SOSIAL DALAM IMPLEMENTASI TANGGUNG JAWAB SOSIAL - Andri Faizal Priyanto; Bandiyono, Agus (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2024)
The development of greenwashing practices carried out by companies has an impact on sustainability and community investments. This study aims to review the impact of greenwashing on investor interest and the growth of sustainability investment. In addition, this study also reviews the role of external social audit in the implementation and disclosure of social responsibility by companies. The research methods used in this study are literature review and content analysis. Literature review is carried out by identifying and synthesizing literature results from various sources of information related to greenwashing and disclosure of sustainability reports. Meanwhile, content analysis is used to add the necessary disclosure information in the discussion review. The results of this study conclude that greenwashing practices reduce investor interest in sustainability investments and external social audits have an important role in the prevention of greenwashing. This research also provides several proposals related to the role of external social audits to support the decline of greenwashing practices by companies. The results of this research are expected to be useful for stakeholders to play a role in the implementation of social responsibility and encourage sustainability investment.